Christoph Ransmayr's 'Flying Mountain' ('Der fliegende Berg'): Neo-modernist poetry in the contemporary German novel - G.A. Frolov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The paper discusses the novel “Flying Mountain” (“Der fliegende Berg”) by Ch. Ransmayr, the famous German writer. The relevance of the study is determined by the fact that the processes of genre and stylistic experimentation, which are characteristic for the development of modern literature in general, are constantly transformed. This requires not only detection of the phenomenon of experiment, but also considering it in the context of changes in the aesthetic paradigms. The study of Ch. Ransmayr's novel “Flying Mountain” has been performed to reveal not only the obvious synthesis of epic and lyrical principles in it, but also with the purpose of showing that the modern aesthetic experiments are primarily related to the complexity of the narrative techniques linking the signs of different literary trends: realism, modernism, and postmodernism. This purpose has been achieved through the integrated use of the methods of literary history and discourse analysis. The paper gives a number of examples to prove that the narrative strategy in Ch. Ransmayr's novel “Flying Mountain” defines the principles of various aesthetic paradigms that are updated by the writer in order to show the diversity of life itself. The modernist principles aim to underline the subjective nature of the narrative, while the postmodernist ones are focused on the approval of the idea of diversity and fullness of life itself. The rhythmic-tone organization of the text of the novel is one of the main ways of expressing the eternal movement of life as opposed to the death. It has been concluded on the basis of the research results that Ch. Ransmayr's novel “Flying Mountain” is a neomodernist metanarrative. These results are important for understanding the specifics of the development of the contemporary German literature.